Effects of B contents on the microstructure and wear resistance of hypereutectic Fe-Cr-C hardfacing alloy coating. (20th September 2019) - Wang, Jibo; Lu, Jianxiang; Xing, Xiaolei; Zhou, Yefei; Liu, Shaocun; Qi, Xiaowen; Yang, Qingxiang
Abstract: In this work, the effects of boron (B) content on the microstructure and wear resistance of the hypereutectic Fe-Cr-C hardfacing alloy coating were investigated via open-arc welding. First, the phase precipitation of the coatings with different B contents was calculated by ThermoCalc software. The microstructures of the coatings were then observed by metallographic microscopy and field emission scanning electron microscopy. The phase composition and structure of the coatings were determined by x-ray diffraction. In addition, the hardness of the coatings and the hard phases in the coatings were determined using a Rockwell hardness tester and a nanoindentation system. Finally, the wear resistances of the coatings with different B contents were measured by the abrasive belt and impact frictional wear methods. The results show that M2 B boride can be precipitated before M7 C3 carbide in the hypereutectic Fe-Cr-C hardfacing alloy coatings when the B content is more than 1.0 wt%. The primary M7 C3 carbides in the coatings can be refined by Element B. When the B content in the coating is 1.0 wt%, the average size of the primary M7 C3 carbide is refined from 40 to 10 μ m. The microhardness of M2 B boride is 28.7 GPa, which is significantly higher than that of the primary M7 C3 carbide (18.7 GPa). The wear resistance of the coating is highest when the B content is 1.0 wt%. The wear resistance of the coating is not increased further with increasing B content.